2021
DOI: 10.1007/s00520-021-06611-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of anxiety and spiritual well-being on the care burden of caregivers of cancer patients during the COVID-19 pandemic

Abstract: Objectives The COVID-19 pandemic has adversely affected the caregivers of people with all chronic diseases, including people with cancer (PWC). This study was conducted to determine the impact of anxiety and spiritual well-being on the care burden of caregivers of PWC during the COVID-19 pandemic. Design This cross-sectional descriptive study included 250 caregivers of hematology and oncology patients registered with a cancer support association. All participants comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 45 publications
3
18
0
Order By: Relevance
“…Our results suggested that the caregiver burden decreased with an increase in the education level, which was consistent with the findings from the studies by Akkuş et al (33) and Eskin et al (34) on caregivers of patients with cancer. A higher education level is associated with an increased awareness about the disease and with the required measures adopted for delivering proper care, thus reducing the caregiver burden.…”
Section: Discussionsupporting
confidence: 93%
“…Our results suggested that the caregiver burden decreased with an increase in the education level, which was consistent with the findings from the studies by Akkuş et al (33) and Eskin et al (34) on caregivers of patients with cancer. A higher education level is associated with an increased awareness about the disease and with the required measures adopted for delivering proper care, thus reducing the caregiver burden.…”
Section: Discussionsupporting
confidence: 93%
“…SWB is an important factor in coping with the difficulties that caregivers experience during the care of patients with cancer. SWB is a concept that includes both religion and spirituality (Akkuş et al, 2022 ). More religion or spirituality was associated with lower depressive symptoms and less personality disorder (Power & McKinney, 2014 ), less post-traumatic stress and perceived stress (Arévalo et al, 2008 ) also this may affect caregiver burden.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed in our study that caregivers of cancer patients intensely felt the fear of infecting themselves and infecting their patients with the Covid-19 virus. In the previous studies, caregivers reported that they experienced the fear of infection because they thought that the Covid-19 virus would affect the treatment processes of cancer patients [16,17]. Caregivers further told that they feared that their patients would be infected with the virus more easily because the treatments they received suppressed the immune system [4].…”
Section: Discussionmentioning
confidence: 99%